2009
DOI: 10.1680/geot.7.00118
|View full text |Cite
|
Sign up to set email alerts
|

A water retention model for deformable soils

Abstract: The paper presents an experimental study on water retention behaviour of two reconstituted soils, a silty clay (Speswhite kaolin) and a sandy clayey silt ( Barcelona silt) and two compacted soils, a silty clay ( Speswhite kaolin) and a silty sandy gravel (Adige river embankment). These soils were used with the aim of encompassing a wide range of soil types and soil fabrics. Specimens were subjected to drying and wetting 'hydraulic' paths by removing or adding water under zero total stress and to 'mechanical' w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(144 citation statements)
references
References 16 publications
6
122
2
1
Order By: Relevance
“…Many studies were conducted to assess the influence of different factors on the water retention properties of the soil in geotechnical engineering applications. Numerous investigations (e.g., [23][24][25][26]) noted that the void ratio, water content, and stress state of a soil have a strong influence on the SWCC. Standard laboratory equipment based on the axis translation technique, such as the pressure plate, volume extractor, suction-controlled oedometer, modified triaxial apparatuses, and standard tensiometers, are the most common devices used to control or measure matric suction.…”
Section: Methods Used For Determination Of Soil-water Characteristic mentioning
confidence: 99%
“…Many studies were conducted to assess the influence of different factors on the water retention properties of the soil in geotechnical engineering applications. Numerous investigations (e.g., [23][24][25][26]) noted that the void ratio, water content, and stress state of a soil have a strong influence on the SWCC. Standard laboratory equipment based on the axis translation technique, such as the pressure plate, volume extractor, suction-controlled oedometer, modified triaxial apparatuses, and standard tensiometers, are the most common devices used to control or measure matric suction.…”
Section: Methods Used For Determination Of Soil-water Characteristic mentioning
confidence: 99%
“…The water retention curve expressed in terms of water content or degree of saturation and suction is hysteretic, stress path dependent (void ratio) and depends on the pore network [1,10,16,18,19,21,23,25,27,28,31]. To properly describe its evolving water retention character, a multimodal retention model is proposed in the paper by considering a linear superposition of two subcurves of the van Genuchten [33] type.…”
Section: Introductionmentioning
confidence: 99%
“…The air entry values in this approach were all determined directly from the available experimental data, and the slope of SWRC was considered to be almost the same under different net stress levels (consistent with the assumptions in the previous studies [see, e.g. Tarantino (2009)]. Therefore, the coupling parameter was the only parameter which was found from calibrating the proposed equation with the experimental data at zero net stress level.…”
Section: Corey-brooks Relationship For Capillary Pressure and Bishop'mentioning
confidence: 87%
“…One major characteristic of unsaturated soils is the soil water retention curve (SWRC), which specifies capillary pressure value associated with the water saturation degree. In recent years, experimental evidences have clearly shown that soil water retention curves are dependent on the stress level (Romero and Vaunat 2000;Karube and Kawai 2001;Gallipoli et al 2003b;Tarantino and Tombolato 2005;Nuth and Laloui 2008;Tarantino 2009;Uchaipichat 2010). Tarantino (2009) has considered the dependency of air entry value on stress level and has offered a SWRC equation for deformable media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation